Eccentric training improves tendon biomechanical properties: A rat model12. Issue 1 (30th July 2012) - Kaux, Jean‐François; Drion, Pierre; Libertiaux, Vincent; Colige, Alain; Hoffmann, Audrey; Nusgens, Betty; Besançon, Benoît; Forthomme, Bénédicte; Le Goff, Caroline; Franzen, Rachel; Defraigne, Jean‐Olivier; Cescotto, Serge; et al.
Abstract The treatment of choice for tendinopathies is eccentric reeducation. Although the clinical results appear favorable, the biomechanical changes to the tissue are not yet clear. Even if the mechanotransduction theory is commonly accepted, the physiology of tendons is not clearly understood. We aimed to better define the biomechanical and histological changes that affect healthy tendon after eccentric and concentric training. This study compared the effects of two methods of training (eccentric [E] training and concentric [C] training) with untrained (U) rats. The animals were trained over a period of 5 weeks. The tricipital, patellar, and Achilles tendons were removed, measured and a tensile test until failure was performed. A histological analysis (hematoxylin and eosin and Masson's trichrome stains) was also realized. There was a significant increase in the rupture force of the patellar and tricipital tendons between the U and E groups. The tricipital tendons in the control group presented a significantly smaller cross‐sectional area than the E‐ and C‐trained groups, but none was constated between E and C groups. No significant difference was observed for the mechanical stress between the three groups for all three tendons. Histological studies demonstrated the development of a greater number of blood vessels and a larger quantity of collagen in the E group. The mechanical properties of tendons in rats improve after specific training, especially following eccentric training. Our results partly explained how mechanical loading, especially in eccentric mode, could improve the healing of tendon. © 2012 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 31:119–124, 2012